Mitotic stages of Prosthenhystera n. sp. (Digenea: Callodistomidae), a gallbladder parasite of Bryconamericus ikaa from the lower Iguazú River - Montes, Martín Miguel (2020)
Imágenes de la meiosis de Prosthenhystera.